2017
DOI: 10.1093/geroni/igx023
|View full text |Cite
|
Sign up to set email alerts
|

Grandparenting in the United States

Abstract: Grandparenting varies enormously in the United States and here we discuss that growing diversity. Relying on exchange and reciprocity, feminist, and political economic theoretical perspectives, we begin by exploring the increasing need for grandchild care and assistance in the United States and the dearth of federal and employer supports for working families. Assessing the impact of sociodemographic trends, notably the rise in single parenting and the increase in employment among grandparents, we assess the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 53 publications
2
48
1
1
Order By: Relevance
“…About 35% of caregivers are 50 to 64 years old, and another 19% are 65 years and older ( AARP & National Alliance for Caregiving, 2020 ). Further, reliance on grandparents has grown in the United States in response to increased numbers of single parents, absent parents, or parents with mental health and substance abuse problems ( Meyer & Kandic, 2017 ). During this pandemic, older caregivers have continued essential caregiving responsibilities, despite disruptions in usual health and social care arrangements and living with increased risk for exposure to the virus themselves.…”
Section: A Productive Aging Perspective On a Diverse Older Populationmentioning
confidence: 99%
“…About 35% of caregivers are 50 to 64 years old, and another 19% are 65 years and older ( AARP & National Alliance for Caregiving, 2020 ). Further, reliance on grandparents has grown in the United States in response to increased numbers of single parents, absent parents, or parents with mental health and substance abuse problems ( Meyer & Kandic, 2017 ). During this pandemic, older caregivers have continued essential caregiving responsibilities, despite disruptions in usual health and social care arrangements and living with increased risk for exposure to the virus themselves.…”
Section: A Productive Aging Perspective On a Diverse Older Populationmentioning
confidence: 99%
“…Compared to the United States, Silverstein et al (2010) found a greater prevalence of detachment, but a lower likelihood of disharmony and ambivalence in emotional relationships of older parents and children in Germany. The proportion of German grandparents providing childcare, however, corresponds to the United States and Continental European averages (Hank & Buber, 2009; Harrington Meyer & Kandic, 2017). 1 A considerable share of grandparents also supports their grandchildren financially (one-off rather than regular transfers; Hoff, 2007), and the grandparent role is generally highly valued and desired among older Germans (Mahne & Motel-Klingebiel, 2012).…”
Section: The German Contextmentioning
confidence: 99%
“…Pada umunya nenek mengasuh cucunya dengan sukarela karena beranggapan bahwa perlu memanfaatkan masa tua untuk cucu mereka. Faktor lain yang mempengaruhi adalah sudah terbentuknya kelekatan dengan cucu dan tidak adanya tekanan diantara keduanya (Meyer and Kandic, 2017).…”
Section: Tema 2 : Alasan Mengasuh Cucuunclassified